Historiografi Indonesia: Melacak Pengaruh Islam Sebelum Masa Kolonial - Lukmanul Hakim; Abu Haif (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2019)
This paper aims to describe and analyze the influence of Islam on the historiography of Indonesia before the colonial period. The method used is a historical method using a historiographic approach. The influence of Islam on the historiography of Indonesia before independence is to give the color of Islam to the historiography of Indonesia, this can be seen by the stories that existed before Islam colored by Islam, the shape and pattern of Indonesian historiography were influenced by Arabic and Persian historiography. With the arrival of Islamic Indonesian Historiography, it developed in all aspects of society, from the palace level to the surau, hut, mosque, pesantren or the house of a cleric, whose authors were known as scholars and poets. Historical questions and historiographic functions after the arrival of Islam underwent a change, which previously questions about the past only revolve around the king and the structure of the story that is cultured to the king, with the coming of Islamic influence historical questions develop to the teachings of religion, scholars, Sufis and heroes-¬ hero of Islam. The role of reporting in the history of Indonesian history with the inclusion of Islam as an Islamic da'wah.